Single-arm trial of neoadjuvant ipilimumab plus nivolumab with chemoradiotherapy in patients with resectable and borderline resectable lung cancer: the INCREASE study - Tanja D de Gruijl; Lilian J Meijboom; Teodora Radonic; Chris Dickhoff; Idris Bahce; Sayed M S Hashemi; Daniela E Oprea-Lager; Ezgi B Ulas; Suresh Senan; Famke L Schneiders; Joris Veltman; David J Heineman; et al. (Journal for ImmunoTherapy of Cancer)
Background In non-small cell lung cancer (NSCLC), chemoradiotherapy (CRT) yields pathological complete response (pCR) rates of approximately 30%. We investigated using ipilimumab plus nivolumab (IPI-NIVO) with neoadjuvant CRT in resectable, and borderline resectable NSCLC.Methods This single-arm, phase-II trial enrolled operable T3-4N0–2 patients with NSCLC without oncogenic drivers. Primary study endpoints were safety, major pathological response (MPR) and pCR. Treatment encompassed platinum-doublet concurrent CRT, IPI 1 mg/kg intravenous and NIVO 360 mg intravenous on day-1, followed by chemotherapy plus NIVO 360 mg 3 weeks later. Thoracic radiotherapy was 50 or 60 Gy, in once-daily doses of 2 Gy. Resections were 6 weeks post-radiotherapy.Results In a total of 30 patients in the intention-to-treat (ITT) population, grades 3–4 treatment-related adverse events (TRAEs) occurred in 70%, one TRAE grade 5 late-onset pneumonitis on day 96 post-surgery (1/30, 3.3%) occurred, and one non-TRAE COVID-19 death (1/30, 3.3%). pCR and MPR were achieved in 50% (15/30) and 63% (19/30) of the ITT; and in 58% (15/26) and 73% (19/26) of the 26 patients who underwent surgery, respectively. Postoperative melanoma was seen in one non-pCR patient. The R0 rate was 100% (26/26), and no patient failed surgery due to TRAEs. In peripheral blood, proliferative CD8+ T cells were increased, while proliferative regulatory T cells (Tregs) were not. On-treatment, pCR-positives had higher CD8+CD39+ T cells and lower HLA-DR+ Tregs.Conclusions Neoadjuvant IPI-NIVO-CRT in T3-4N0–2 NSCLC showed acceptable safety with pCR and MPR in 58% and 73% of operated patients, respectively. No patient failed surgery due to TRAEs.Trial registration number NCT04245514.